Democracy in unequal times: how economic inequality influences democratic backsliding - Jia, Yujie (2024)
A prevalent view holds that prolonged severe economic inequality is a potential cause of democratic backsliding, as the concentration of resources in the hands of a few comes at the expense of the majority, directly challenging the core principles of democracy. Despite this, little work has been done to thoroughly examine how economic inequality influences democratic backsliding. This study delves into the heterogeneous political consequences of different forms of economic inequality. We adopt a multidimensional measure of democracy and employ dynamic models to explore both linear and non-linear relationships. Using five-year panel data from 140 countries over the period 1970-2020, we observe that income inequality has no significant effect on the quality of democracy, whereas worsening wealth inequality undermines it. We also find evidence of high persistence in democracy and that the erosion of democracy by wealth inequality deepens over time. No evidence supporting a non-linear effect for either type of economic inequality. Notably, the adverse effect of wealth inequality is primarily found in democracies. These findings suggest that in the context of democracy in unequal times, there is a close association between wealth inequality and democratic backsliding in democratic countries, whereas income inequality does not.